The Form of Alawiyyin Relations in Social Life Based on Noble Values and Hereditary Line - Ikhtiar Hatta (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
This study suggests the application of the syiar method as part of the relationship between the Alawiyyin to build their unity in living their social life with other communities. This study applies a historical approach that looks at how the Alawiyyin started with the construction of a social arena through an operational life order with Islamic faith and the noble values of the Alawiyyin, how the Alawiyyin lives and maintain the existing order in social relations. The results shows that through the institutions, norms, and symbolic apparatus covering the life of the Alawiyyin. Functionally, it could support their existence as a foreign Alawiyyin community in Maluku. Furthermore, this study reveals that the Alawiyyin builds their social arena by relating religious life and daily life practices. Through the teaching mode of the life of his ancestors, the prophet Muhammad, can form belief and devotion to Allah. In addition, it contributes positively to maintaining the lineage (genealogy) of the Alawiyyin in the middle of the arena of social life that continuously mix through the process of amalgamation. Apparatus that supports stability, commitment to love/loyalty of those around them is maintained through practice, grave pilgrimage, reading ratib, dhikr, proselytization, becoming a muhibbin, tasawuf, tawassul, barsanji, and kafaah marriage.